The impact of the pandemic crisis on employment in the context of urbanization - Stan, Mari-Isabella (Technium Social Sciences Journal, 2022)
The level of economic and social development of a country is closely linked to the degree of urbanization. Continuous urbanization will bring new opportunities for and challenges to sustainable development, which is closely correlated with the general level of economic and social development. Thus, the global urbanization trend has been accompanied by changes in employment, representing both a goal and a means of sustainable development at the level of all the branches of national economies. A major test for all the countries was the crisis caused by the Covid-19 pandemic, which severely impacted the labor market in Europe and beyond. This research aims to produce an overview on the employment situation in urban and rural areas for 31 countries in Europe, as well as on the impact of the Covid-19 pandemic on employment for the analyzed countries. Although cities are development centers for their countries in terms of economics and quality of life, there is also a need to improve the living conditions of rural residents and increase the attractiveness for all population segments, in order to reduce the rural-urban imbalance in terms of employment opportunities.